KONSEP MAHABAH DALAM PERSPEKTIF TAFSIR MAUDHU’I - Samud Samud (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2017)
Mahabah, is in Arabic Mah}abbah derived from the word ah}abba-yuh}ibbu-mah}abbatan, which in language means deep love, love, or deep love. The Mahabah is defined as "the total inclination of the heart to something, the attention to it more than the self, the soul and the possessions, the attitude of the self in receiving both outwardly and inwardly, its orders and prohibitions; and self-acknowledgment of the lack of love given to him. Man is one of God's creatures who have been given a sense of love, so that man is able to make himself a being who can love his neighbor. With that feeling of love also humans can love and get closer to God. But what happens in the present time some people in the name of love to do something wrong, it is not expected by the teachings of Islam. The concept of Mahabah in the Qur'an is the view of the Qur'an in this case is the Ottoman manuscripts of the Mahabah and the things associated with it are done by collecting passages that discuss the Mahabah.